Chemical, Semi-chemical and Chemi-mechanical Pulps from Casuarina equisetifolia - Guha, S. R. D.; Karira, B. G. (Indian Forester, 1981)
Laboratory scale experiments on production of chemical (Kraft pulping) semi-chemical and Chemi-mechanical pulps are described in this paper. It is observed that pulps of satisfactory yield and strength properties could be obtained from the Casuarina equisetifolia similar to that of Eucalyptus grandis and Eucalyptus citriodora for wrapping paper, corrugating medium and core of the duplex boards.